The Transferable Skills of a Manager - Yntema, Theodore O. (Academy of Management Journal, 1960)
Discusses the transferable skills and knowledge of a manager. Discussion on interpersonal relations and business communication; Details of managerial training and competency in corporate planning; Contribution of creativity and team effort in the success of corporate executives.